2018
DOI: 10.1108/tqm-10-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental comfort based (ECB) methodology as a tool for preparing Kaizen application in a catering service company

Abstract: Purpose The purpose of this paper is to develop a methodology that is based on the concept of environmental comfort and can serve as a tool that can help companies and employees to implement Kaizen projects. This methodology focuses on the worker’s participation in analyzing and developing improvements related to their workplace. Design/methodology/approach This research is focused on the development of a methodology that encourages worker participation in improvement activities, through the analysis of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In the analysis of Kaizen in the preceding literature, most of the research initiatives were focused with the following issues or themes: systematic literature reviews (Álvarez-García et al , 2018; Carnerud et al , 2018) of Kaizen articles and origins and characteristics of Kaizen philosophy (Méndez and Vila-Alonso, 2018; Chung, 2018; Chiarini et al , 2018), case studies and implementation in manufacturing (Fonseca and Dominguez, 2018) and services (Chen, 2018), drivers and barriers in Kaizen application (Alvarado-Ramírez et al , 2018; Jaca et al , 2018; Marín-García et al , 2018), Kaizen events and their CSFs (González-Aleu et al , 2018). Moreover, Suárez-Barraza et al (2011) found that Kaizen appears to refer to two kinds.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the analysis of Kaizen in the preceding literature, most of the research initiatives were focused with the following issues or themes: systematic literature reviews (Álvarez-García et al , 2018; Carnerud et al , 2018) of Kaizen articles and origins and characteristics of Kaizen philosophy (Méndez and Vila-Alonso, 2018; Chung, 2018; Chiarini et al , 2018), case studies and implementation in manufacturing (Fonseca and Dominguez, 2018) and services (Chen, 2018), drivers and barriers in Kaizen application (Alvarado-Ramírez et al , 2018; Jaca et al , 2018; Marín-García et al , 2018), Kaizen events and their CSFs (González-Aleu et al , 2018). Moreover, Suárez-Barraza et al (2011) found that Kaizen appears to refer to two kinds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the identified practices are not analogous and lack evenness. For example, Prajogo and Sohal (2004) state, based on Jaca et al (2018), the most relevant enablers for attaining a CI culture in companies are: top management support and commitment, strategic focus on CI through the definition of an appropriate set of goals and objectives, using the right methodology to implement CI throughout the whole organization, creating and sustaining a CI culture, employee support and commitment, good information, communication and knowledge-transfer systems and having a CI management and follow-up system to track the CI. Other scholars (Marín-García et al , 2018) also identified 14 facilitators: good communication, assertive behavior, self-efficacy, knowledge management, training, leadership, compensation systems, intrinsic motivation, feedback about suggestions, participating in the implementation, protocol, enterprise culture, group composition and sufficient resources.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another selected paper is the one presented by Jaca et al (2018). It links Kaizen to an environmental methodology as a driver to implement Kaizen in Spanish companies.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…Whilst empirical tests linking these concepts to specific aspects of job performance remain rare, the model has proven to be popular in terms of informing the different criteria to consider during a workplace evaluation (e.g., Jaca et al, 2018;Naccarella et al, 2018).…”
Section: Environmental Comfortmentioning
confidence: 99%